Attitudes Toward Gay Men and Lesbian Women Moderate Heterosexual Adults’ Subjective Stress Response to Witnessing Homonegativity - Hahn, Hunter; Seager van Dyk, Ilana; Ahn, Woo-Young (Frontiers in Psychology, 2020)
Minority stress theory posits that members of a stigmatized group, such as sexual minorities (lesbian, gay, bisexual, and other non-heterosexual individuals), are particularly subject to ill effects of minority-specific events (stressors), including overt homonegativity. Although adverse effects of homonegativity are well documented for sexual minorities, little is known about effects of witnessing homonegativity on heterosexual individuals. As a growing number of heterosexual individuals hold accepting views of sexual minority individuals, some detrimental effects of homonegativity may extend to heterosexual individuals. For example, prior studies demonstrate that when racial majority-group members witness discrimination against minority-group members, they may experience stress response, particularly if they hold positive attitudes toward the minority-group. In this experimental study, 263 heterosexual adults (mean age = 34.47 years, SD = 9.67, 51.7% female) were randomized to either witness homonegativity or to a control condition. Participants rated subjective stress on a 0-100 visual analogue scale both immediately before and after the film-based induction. Participants also completed a measure of their attitudes toward gay men and lesbian women. Moderation analyses indicated that participants who were more accepting of gay men and lesbian women experienced greater stress after the induction than those with less accepting views. Implications and limitations of these findings are discussed.